Temporal CT of the Pneumatized Petrous Apex: Associated Anomalies and the Relationship with Tinnitus and Vertigo - Sayit, Asli Tannvermis; Elmahi, Muzaffer; Terzi, Yuksel (Aves, 2018)
Introduction: The aim of the present study was to determine concomitant congenital anomalies and variations of the temporal bone in patients with a pneumatized petrous apex and to investigate the relationship of non-pulsatile subjective tinnitus and peripheral vertigo with petrous apex pneumatization. Methods: Temporal multidetector computed tomography (MDCT) images of 2120 patients were obtained from the hospital's digital database between 2009 and 2017. The MDCT scans were performed for various preliminary diagnoses including non-pulsatile subjective tinnitus, peripheral vertigo, hearing loss, otitis, and otalgia. Petrous apex pneumatization was detected in 192 patients. Twenty-six patients with temporal bone trauma were excluded from the study. One hundred sixty-six patients were included in the study. Temporal bone MDCT images were evaluated for concomitant congenital anomalies and variations. Results: The incidence of diffuse petrous apex pneumatization was 9%. Excessive temporal bone pneumatization and high jugular bulb (JB) were found to be most prevalent in patients with petrous apex pneumatization. There were statistically significant differences between petrous apex pneumatization and peripheral vertigo (p=0.009). However, there were no statistically significant differences between petrous apex pneumatization and non-pulsatile subjective tinnitus (p=0.62). Conclusion: The most common variation was the high JB, and the most common anomaly was the dehiscent internal carotid artery in patients with petrous apex pneumatization. Moreover, there was no statistically significant relationship between non-pulsatile subjective tinnitus and unilateral or bilateral petrous apex pneumatization.
Keywords: Petrous Apex Pneumatization; Tinnitus; Vertigo; Temporal; Multidetector Computed Tomography